Separation of Powers and Judicial Independence in Kazakhstan and Germany: A Comparative Legal Analysis - Abdrassulov , Е.Б.; Akhmet, Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article presents a comparative legal analysis of the system of separation of powers and the independence of the judiciary in the Republic of Kazakhstan and the Federal Republic of Germany. The relevance of the research lies in the fact that, in a democratic state, ensuring institutional independence of the judiciary and maintaining a balanced interaction among the branches of power have become increasingly important. The article examines the constitutional foundations, the theoretical and historical evolution of the principle of separation of powers, and the specific features of its implementation in the legal systems of both countries. Particular attention is given to Germany’s federal structure, the role of the Constitutional Court, judicial appointment procedures, and legal mechanisms that guarantee judicial independence. In addition, the development of the judicial system in Kazakhstan, the functions of the Supreme Court and the Constitutional Court, judicial reforms, and the formation and role of the institution of legal positions are analyzed. The article also compares the role of courts in legal development and the extent to which judicial decisions are recognized as sources of law in both countries. The authors explore the possibilities and specific aspects of applying German experience in the context of Kazakhstan and offer recommendations aimed at strengthening the independence of the judiciary in the Republic of Kazakhstan. The findings contribute both theoretically and practically to the improvement of the national legal system.